Geodetic Versus Geophysical Perspectives of the 'Gravity Anomaly' - Hackney, R.; Featherstone, Will (Blackwell Publishing Ltd, 2003)
A 'gravity anomaly' is essentially the difference between the gravitational acceleration caused by the Earth's masses and that generated by some reference mass distribution. However, there are numerous subtleties to the definition and, moreover, to the practical realization of a 'gravity anomaly'. An attempt is made here to clarify the definition of a 'gravity anomaly' from the geodetic and geophysical perspectives, point out some of the key differences in terminology and philosophy and to identify some of the problems remaining in its practical realization from a variety of observation types. It is argued that if the 'gravity anomaly' is defined and realized in a rigorous and consistent manner, this may lead to the improvement of its use in both geodesy and geophysics